Kur’an’da inabe kavramı - Öncel, Müyesser (My University, 2006)
Kur’an insanları Allah’ın yoluna iletmek için gönderilmiş son kitaptır. Bu bağlamda Kur’an’da insanların Allah’a yönelişini ifade etmek için kullanılan inabe kavramı çalışmamızın konusu olmuştur. Birinci bölümde Kur’an’da, inabe kavramı ile ilgili olan diğer kavram ve kelimeler açıklanmıştır. İkinci Bölümde, Kur’an’da inabe kavramını yeri incelenmiştir. İnabe Kur’an’da on sekiz ayette geçmektedir. Bu ayetlerde insanın Allah’a yönelmesi emredilmekte, başta peygamberler olmak üzere Allah’a yönelenlerin yoluna uyulması istenmektedir. Allah’ın ayetlerinden öğüt alabilmek ve hidayete erebilmek için inabe şart koşulmaktadır. Üçüncü Bölümde ise inabenin tasavvuf ilmindeki yeri açıklanmış ve bu kavramla ilgili olarak yapılan değerlendirmelere değinilmiştir.

ORİENTATION TOWARDS THE HOLY KORAN The Koran is the sacred and last book on which the Religion of Allah is based. The concept of INABE explains and orders all people the unique and sacred way. INABE, orders all people to orientate towards Allah. So, this concept is the basic and essence of all our studies. In the first chapter, the concept of INABE and other concepts and words relative to it are tried to explain. In the second chapter, the place of INABE concept is studied. The word and INABE concept is professed in the eighteen verses of The Koran. These verses order all people to orientate towords Allah. Firstly and principally all these divine and sacred verses were sent to all prophets. It’s expressed that INABE is indispensable for all people and prophets for getting into the way of Allah and receiving advice from the verses of The Koran and reaching eternal and divine happines. In the third chapter, the importance and place of INABE in the mysticism and mystic sciences was studied and given some important explanations and appreciation
Keywords: İslam Dini; Kur’an-ı Kerim; Tefsir